Iqbal and western philosophers (part four) - Abdul Razak, Mohd Abbas (Mission Soft Foundation, 2023)
One of the many orientalists whom Iqbal admired the most was Goethe (1796-1869). In fact, it was admitted by Iqbal himself that in writing the Payam-i-Mashriq he was inspired by Goethe’s famous collection of poems, ‘West-Oestlicher Divan’ (1818) (The West’s Admiration on the East). To Iqbal, Goethe was fair in his criticism of the West of its dominance of the Orient. Goethe’s appeal to the Orient through his Divan was to take a lead in showing the true meaning of spirituality, the real essence of love, faith and conviction to the Occident (Ali, 1988).